Intrigantes Incertitudes. - Hegyi, Lorand; Viola, Eugenio (Fage Éditions [S.l.], 2016)
Barabash, Ruth ; Bollinger, Matt ; Brus, Günter ; Castelli, Guglielmo ; Dessi, Gianni ; Dieterlé, Nicolas ; Dietman, Erik ; Dine, Jim ; Duville, Matias ; Dybvig, Per ; Fabre, Jan ; Fogli, Andrea ; Ghenie, Adrian ; Giletta, Ugo ; Gruber, Erich ; Gunstheimer, Jana ; Hawkins, Allsion ; Holcova, Veronika ; Jaune, Oda ; Joatton, Marine ; Kovacheva, NINA ; Kraijer, Juul ; Bul, Lee ; Levasseur, Iris ; Levini, Felice ; Lhopital, Christian ; Maris, Maude ; Martensen, Peter ; Molodkin, Andreï ; Mosbacher, Alois ; Mintean/Rosenblum ; Nitsch, Hermann ; Oppenheim, Dennis ; Révész, Laszlo Laszlo ; Seinturier, Pierre ; Smith, Kiki ; Toguo, Barthélémy ; Trenet, Didier ; Trenkwalder, Elmar ; Vasquez de la Horra, Sandra ; Verschaere, Fabien
boek